STRATEGI PENINGKATAN PENGGUNAAN PRODUK UMK PASKA UU CIPTA KERJA - Adhi Prasetyo Satrio Wibowo (Pusat Kajian Anggaran, 2022)
The policy of 40 percent spending on goods/services is one of the 9 points of point Act Number 11 of 2020 on Job Creation (CIPTAKER Act) is a government’s effort to support Micro, Small, and Medium Enterprises (MSMEs) business development. For this reason, the objectives of this study are two. First, examine how MSE products are utilized from domestic production to the implementation of the Job Creation Act. Second, the challenges faced by the government, especially the empowerment of MSEs afterward in order to increase the utilization of domestic MSMEs. The research method was developed using normative juridical methods through literature studies that examine primary and secondary legal materials. Furthermore, the data analysis technique used in this study was carried out using a qualitative method, through the collection of written legal materials classified according to the order of the problems identified. This paper is compiled using qualitative approach methods and literature studies. The results have shown there are several improvements that should be made by the government related are improvements that still have to be made by the government related to roadmap making, optimizing the role of assistants, the active role of the Ministry of Cooperatives and MSMEs as the leading MSE sector strengthening the role of the inspectorate.